Urgensi Pengadaan Bilik Asmara Bagi Narapidana Yang Telah Menikah - Wiwin Wiwin (Jurnal Litigasi Amsir, 2023)
Sexual rights are fundamental human rights that must be protected and upheld by the state. The state's responsibility in this regard faces specific challenges because the Family Visit Leave (Cuti Mengunjungi Keluarga-CMK) mechanism has not been sufficient to meet the sexual needs of married inmates. Therefore, an alternative mechanism is needed to fulfill the sexual rights of inmates, in the form of providing love rooms (bilik asmara). This research aims to explore the urgency of establishing love rooms for married inmates. The study employs a normative research approach with juridical and conceptual approaches. The findings indicate that establishing love rooms in correctional facilities is urgent to fulfill the sexual rights of married inmates. The provision of love rooms aligns with the second principle of Pancasila, which emphasizes the fulfillment of sexual rights as a commitment of the state to humanize its citizens. Establishing love rooms is also crucial to fulfill constitutional rights of citizens and the state's responsibilities concerning marriage. Ultimately, the provision of love rooms will contribute to maintaining family harmony and meeting the sexual needs of inmate couples.